Implementasi Media Pembelajaran Audio Visual pada Mata Pelajaran Fiqih di MI Raudhatut Tholibin Pasiran Mumbang Jaya - Nuryanto, Nuryanto; Solehah, Nisa Zumrotus (Tapis: Jurnal Penelitian Ilmiah, 2024)
The purpose of this study was to describe the implementation of audio-visual learning media in fiqh class V, the obstacles faced and the efforts made by the school and the educators concerned. To achieve the above objectives, in this research the researcher used descriptive qualitative research. This research data was obtained through observation, interviews, and documentation techniques. The data analysis techniques used in this research are data reduction, data display (data presentation), and verification (concluding). The data validity techniques used are extended participation, observation, triangulation, and reference materials. The results showed that the implementation of audio-visual learning media in the fiqh subject of class V MI Raudhatut Tholibin has been going quite well, it's just that in practice educators still encounter obstacles such as limited creative power from the limited ability to use applications for making teaching materials, limitations in the installation of instructional media, limitations in technical matters when dysfunction or errors occur when learning takes place and the limited number of media resulting in clashes in the use of media between one educator and another educator. The solution is to provide technical guidance for class teachers regarding the production of teaching materials, installation of instructional media, error handling, and scheduling of the use of audio-visual learning media.